The British Nationality and Borders Bill and the international protection of refugees in the light of the concept of community interest in international law - Kuźniar, Dagmara (Review of European and Comparative Law, 2022)
The crisis that Europe faced in 2015 has never been resolved and countries have adopted different strategies to deal with the influx of migrants . Some of them raise serious legal doubts for good reason. One of the new national solutions currently in the process of passing is the new migration plan announced by the United Kingdom in the Nationality and Borders Bill last year. The aim of the reform is to improve the British asylum system and to fight effectively illegal immigration and people smuggling.The aim of the article is to present the most important assumptions of the British reform in the field of grant- ing refugee status. The analysis would allow to assess the compliance of the designed solutions with international obligations, the fulfilment of which should form the basis of the asylum policy of each State being a party to the 1951 Convention relating to the Status of Refugees. The main aim of the article, however, is to draw attention to the fact that the international protection of refugees should be equated with community interests and referring to the individual interest of the State is an erroneous and dangerous assumption.